Tertiary students maintaining control over depression, anxiety, and stress during the pandemic—An emerging market perspective - Ivascu, Larisa; Arulanandam, Benedict Valentine; Artene, Alin; Selvarajah, Prema; Ching, Lim Fung; Ragunathan, Chitra Devi (Frontiers in Psychology, 2022)
The higher education sector was affected by this pandemic, managing enduring challenges since early 2020. Institutions of higher learning (IHL) are prepared to address unsurmountable challenges to ensure that students are not deceived and are being given the proper nurture, coupled with adherence to syllabuses. Simultaneous, the Covid-19 pandemic has caused unscrupulous pressure on students of these institutions. The psychological waves are creating mammoth consequences, affecting the beneficiaries of the higher education system and their families. In recent years, with limited studies on psychological impact among tertiary students on a cross-country basis, general self-efficacy and the degree of coping strategies, we were motivated to investigate the degree of depression, anxiety and stress (DAS), among this cohort of students encompassing the pre-university/Diploma, 1st – 4th-year undergraduate and postgraduate students from private universities in Malaysia, Indonesia, India, Southern Africa and China, representing the emerging economies. A cross-sectional survey was conducted, followed by quantitative analysis. The objective of this study is to recognise whether there is a relationship between the psychological impact of DAS and the coping strategies adopted by the undergraduate students responding during the lockdown. Furthermore, our study employs the general self-efficacy scale (Schwarzer & Jerusalem, 1995), as a moderator to identify the strategies that exist that are intended to mitigate the level of DAS. The findings of this study revealed that with the sample size of 397, DAS lacked any severe impact on students across gender, country, household income and level of education. DAS was established to be well managed with a coping strategy and self-efficacy established. This study resulted in a deeper understanding of DAS among undergraduates in emerging economies and their degree of coping behavior, providing a glimpse of the approach of millennials to handle DAS during the pandemic.